Sleep quality and the integrity of ascending reticular activating system – A multimodal MRI study - Viktória Kokošová; Lubomír Vojtíšek; Marek Baláž; Silvia Mangia; Shalom Michaeli; Pavel Filip (Heliyon)
Sleep is crucial for maintaining brain homeostasis and individuals with insufficient sleep are prone to more pronounced brain atrophy as compared to sufficiently sleeping peers. Moreover, sleep quality deteriorates with ageing and ageing is also associated with cerebral structural and functional changes, pointing to their mutual bidirectional interrelationship. This study aimed at determining whether sleep quality and age, separately, affect brain integrity and subsequently, whether sleep significantly modulates the effect of age on brain structural and functional integrity. 113 healthy volunteers underwent a multi-modal MRI imaging to extract information about the microstructure and function of major nodes of the ascending reticular activating system. Sleep quality was assessed by self-administered Pittsburgh's sleep quality index (PSQI) questionnaire. Subject were divided into good (global PSQI score <5) and poor (global PSQI score ≥5) sleep quality group. Whereas only borderline correlations were found between sleep quality and MRI metrics, age exhibited widespread correlations with both functional and microstructural MRI metrics. The latter effect was significantly modulated by sleep quality in ascending reticular activating system, hypothalamus, thalamus and also hippocampus in MRI metrics associated with iron load, cellularity and connectivity, mainly in the subgroup with poor sleep quality. Ergo, our results indicate sleep quality as a substantial contributor to both microstructural and functional brain changes in ageing and call for further research in this emerging topic.